DAMPAK PEMBANGUNAN JALAN TOL SERANG-PANIMBANG TERHADAP PEREKONOMIAN BANTEN DAN NASIONAL (ANALISIS INTERREGIONAL INPUT-OUTPUT) - Saeful Hidayat (LP2M Universitas Bina Bangsa, 2021)
Serang-Panimbang Toll Road, which connects Serang and Tanjung Lesung Tourism Special Economic Area, is one of the National Strategic Projects (PSN) in Banten. But because of the trade between regions, the impact of development gives rise to interregional spillover effect and interregional feedback effect so that the results are not only received by Banten, but also felt by various regions in Indonesia. Using the IRIO Table 2016, the construction of the Serang-Panimbang Toll Road which costs 713.8 billion rupiah per year, will increase economic output and Gross Regional Domestic Product (PDRB) and create jobs and generate workers' wages in Banten, amounting to 956.3 billion rupiah, 465.5 billion rupiah, 3,805 people and 205.1 billion rupiah a year, respectively. Nationally, the economic impact reached 1.12 trillion rupiah, 0.56 trillion rupiah, 4,672 people, and 0.24 trillion rupiah per year. While the operation of the Serang-Panimbang Toll Road with annual revenues of 1.34 trillion rupiah will have an impact on banten's economy in the form of increasing economic output and GDP, and creating jobs and wages / salaries received by workers, each reaching 1.92 trillion rupiah, 0.88 trillion rupiah, 4,513 people, and 0.20 trillion rupiah a year. The impact on the national economy amounted to 2.29 trillion rupiah, 1.08 trillion rupiah, 6,338 people, and 0.28 trillion rupiah per year